Conceptualising multi-scale thermodynamics within the energy-water-food nexus: Progress towards resource and waste management - Jamileh Fouladi (16932549) (2021)
As the global population increases and economies expand, the demand for energy, water, and food (EWF) resources increases accordingly and thus requires effective resource management. Emphasis on the inherent interlinkages between the resources as promoted by the EWF nexus approach can support efficient resource utilisaiton. The objective of this review is to discuss the role of thermodynamics in evaluating elements within the EWF nexus and the overall system performance, with an emphasis on: (1) multi-scale analysis, and (2) system enhancement through waste minimisation. Thermodynamic approaches reviewed through the literature include energy optimisation represented through heat and mass transfer, pinch analysis, exergy analysis, and emergy analysis. Furthermore, relationships are drawn between the phenomena of entropy, its destruction, and the need to optimise integrated resource systems. In this regard, outcomes of this review illustrate the efficacy of the thermodynamic approaches in achieving such objectives, including the interconnections between them to manage resources within the nexus system. Finally, the review further presents an exergetic approach to quantifying EWF nexus efficiency gains upon the management of entropy in the form of waste, which also contributes to enhanced resource and energy efficiencies. Other Information Published in: Computers & Chemical Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.compchemeng.2021.107375